Welding Quality Engineering Using the Design of Experiment Method (Taguchi's Method) - Anis Siti Nurrohkayati; Dede Zulrahman; Sabaruddin Syach; Muhammad Khairul (Procedia of Engineering and Life Science, 2021)
The technology in modern era and rapid construction sector has made welding an important role in the field of metal engineering and repair. Therefore, the technology in the construction sector, especially in the engineering sector, requires a welding element. Welding is used to combine with metal. Making this connection requires high skill for welder in order to obtain a good quality connection. The aim of this study was to determine the quality of a good welding result using the design of experiment method by looking at the control factor of the electrode, welding amperage, welding method, plate thickness, and welding speed. In addition to control factors, there are also use noise factors such as skill, cleanliness of work pieces, and distance between work pieces. The results of the experiments are based on weld defect criteria and the DOE method with ANOVA calculations, the best welding results are in trial no 7 with an average value of 0.22. Meanwhile, the results of the experiment with welding defects is trial experiment no 2 with a value of 0.64. The factors that influence the quality of the welds are plate thickness, welding amperage, electrodes, and welding method. Meanwhile, the welding speed factor is a factor that does not significantly affect the weld quality.